2014
DOI: 10.1097/rhu.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Hydralazine Associated Pauci-Immune Glomerulonephritis

Abstract: Hydralazine is a medication that has been used to manage hypertension and heart failure. In this case series, we report 4 patients who presented to a large, Midwestern academic medical center on chronic hydralazine therapy with acute kidney injury, nephritic urine sediment on urine microscopy, and the simultaneous presence of autoantibodies suggesting both drug-induced lupus and drug-induced vasculitis. All of them had evidence of pauci-immune glomerulonephritis on kidney biopsy. All the patients reported in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The renal outcomes in patients with hydralazine induced vasculitis have been variable. For example, one series of four patients on chronic hydralazine who developed pauci-immune glomerulonephritis reported that the creatinine for all patients return to baseline or close to baseline within 6 months of follow-up (17). In contrast, in a case series of 17 patients with suspected hydralazine-induced nephritis in which minimum follow-up was 6 months, five patients required dialysis within 2 weeks to 6 years of stopping hydralazine and one patient died of uremia (18).…”
Section: Discussionmentioning
confidence: 95%
“…The renal outcomes in patients with hydralazine induced vasculitis have been variable. For example, one series of four patients on chronic hydralazine who developed pauci-immune glomerulonephritis reported that the creatinine for all patients return to baseline or close to baseline within 6 months of follow-up (17). In contrast, in a case series of 17 patients with suspected hydralazine-induced nephritis in which minimum follow-up was 6 months, five patients required dialysis within 2 weeks to 6 years of stopping hydralazine and one patient died of uremia (18).…”
Section: Discussionmentioning
confidence: 95%
“…It was also reported that hydralazine-induced vasculitis is more common in slow acetylators since hydralazine acetylation will be slower and that gives more chance for a break in tolerance [10]. The risk for developing hydralazine-induced ANCA-associated vasculitis increases with longer duration and higher doses of hydralazine therapy especially in slow acetylators, female patients, and patients with history of thyroid disease [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Renal outcomes for this condition in published cases have been variable, with one case series reporting full recovery in all patients [11] and others reporting around one third to half of patients requiring long-term hemodialysis despite immunosuppressive therapy [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate can be up to 10.4% in patients taking a dose of 200 mg/day for greater than three years [8]. Serum complement levels can be beneficial in differentiating the underlying pathogenesis since C3 and C4 levels are usually normal in PIGN and anti-GBM disease as opposed to the low levels seen in another glomerulonephritis [9,10]. The serological studies may also cause confusion like in our case.…”
Section: Discussionmentioning
confidence: 72%